2021
DOI: 10.3390/cancers13092047
|View full text |Cite
|
Sign up to set email alerts
|

SelectMDx and Multiparametric Magnetic Resonance Imaging of the Prostate for Men Undergoing Primary Prostate Biopsy: A Prospective Assessment in a Multi-Institutional Study

Abstract: Prostate-specific antigen (PSA) testing as the sole indication for prostate biopsy lacks specificity, resulting in overdiagnosis of indolent prostate cancer (PCa) and missing clinically significant PCa (csPCa). SelectMDx is a biomarker-based risk score to assess urinary HOXC6 and DLX1 mRNA expression combined with traditional clinical risk factors. The aim of this prospective multi-institutional study was to evaluate the diagnostic accuracy of SelectMDx and its association with multiparametric magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 56 publications
0
61
0
Order By: Relevance
“…Additionally, MRI has been proven to provide higher staging accuracy compared to digital rectal examination (DRE), allowing a more conservative dissection in patients undergoing RP [ 9 ]. On the other hand, while Gleason grading and histological analysis are based on glandular architecture and the phenotypic appearance of PCa, novel techniques for the high-throughput sequencing of ribonucleic acid (RNA) and deoxyribonucleic acid (DNA) extracted from cancer cells helped to characterize PCa at a genotypic level [ 10 ]. Being the latest studied in PCa genomics, the concept of the heterogeneity of PCa, the intratumoral modifications, clonal and subclonal alterations, microheterogeneity, macroheterogeneity, the multifocal nature of PCa, and the inter-tumoral heterogeneity need to be matched between imaging and molecular pathology, for establishing the clinical implications [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, MRI has been proven to provide higher staging accuracy compared to digital rectal examination (DRE), allowing a more conservative dissection in patients undergoing RP [ 9 ]. On the other hand, while Gleason grading and histological analysis are based on glandular architecture and the phenotypic appearance of PCa, novel techniques for the high-throughput sequencing of ribonucleic acid (RNA) and deoxyribonucleic acid (DNA) extracted from cancer cells helped to characterize PCa at a genotypic level [ 10 ]. Being the latest studied in PCa genomics, the concept of the heterogeneity of PCa, the intratumoral modifications, clonal and subclonal alterations, microheterogeneity, macroheterogeneity, the multifocal nature of PCa, and the inter-tumoral heterogeneity need to be matched between imaging and molecular pathology, for establishing the clinical implications [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to our cohort, their study included more patients with equivocal (PI-RADS 3) MRI lesions; PSA (median 7.8-7.9 ng/mL), age (median 65-67 years), and other clinical variables were similar to those of our cohort [24]. In the future, new tools such as artificial intelligence with radiomics may limit the MRI inter-reader variability and further enhance risk stratification in patients with suspicious MRI [19,20,[25][26][27].…”
Section: Discussionmentioning
confidence: 92%
“…In the era of precision medicine, with new imaging modalities and biomarkers, there is a persisting need to further improve pre-biopsy risk stratification. Negative and positive predictive values of MRI and single biomarkers highly depend on disease prevalence; therefore, combined strategies are needed [2,19,20]. Our model and the corresponding nomogram combining readily available biomarkers, including DRE, age, PI-RADS, and PSAD, revealed that even in patients with suspicious MRI, it is possible to include or exclude, with over 82% accuracy, the probability of significant PCa.…”
Section: Discussionmentioning
confidence: 94%
“…There is still no consensus on whether this screening test can significantly reduce the mortality of prostate cancer (18). In addition, the pathogenesis and molecular mechanisms of invasion and metastasis of prostate cancer are still unclear (19,20). It is important to identify genetic drivers of prostate cancer so that new biomarkers can be developed to stratify the risk and aggressiveness of prostate cancer during screening.…”
Section: Discussionmentioning
confidence: 99%